Observations on the food and feeding habits of Otolithes cuvieri (Trewavas) off Veraval - Manojkumar, P P (Indian Journal of Fisheries, 2011)
Studies on food and feeding habits of Otolithes cuvieri based on 1679 specimens showed that it is a carnivorous feeder, subsisting mainly on Acetes spp., penaeid prawns, deep-sea prawns, fishes, stomatopods, molluscs, isopods, copepods and fish larvae. All size groups preferred crustaceans. The fishes showed preference for teleost fishes as they grew. The intensity of feeding was higher during the premonsoon and postmonsoon months. Feeding intensity was poor in juvenilesand mature fishes.